A Protocol for Nurse-Practitioner Led Cardiovascular Follow-Up After Pregnancy Complications in a Socioeconomically Disadvantaged Population - Aldridge, Emily; Verburg, Petra E.; Sierp, Susan; Andraweera, Prabha; Dekker, Gustaaf A.; Roberts, Claire T.; Arstall, Margaret A. (Frontiers in Cardiovascular Medicine, 2020)
Background: Women who experience pregnancy complications have an increased risk of future cardiovascular disease when compared to their healthy counterparts. Despite recommendations, there is no standardised cardiovascular follow-up in the postpartum period for these women, and the Australian follow-up protocols that have been previously described are research-based. This study proposes a new model of care for a nurse practitioner-led postpartum intervention clinic for women who experience severe hypertensive disorders of pregnancy, gestational diabetes mellitus requiring medication, severe intrauterine growth restriction, idiopathic preterm delivery, or placental abruption, in a socioeconomically disadvantaged population. Methods: All women receiving antenatal care or who deliver at the Lyell McEwin Hospital, a tertiary acute care facility located in the northern Adelaide metropolitan area, following a severe complication of pregnancy are referred to the intervention clinic for review at 6 months postpartum. A comprehensive assessment is conducted from demographics, medical history, diet and exercise habits, psychosocial information, health literacy, pathology results and physical measurements. Subsequently, patient-specific education and clinical counselling are provided by a specialised nurse practitioner. Clinic appointments are repeated at 18 months and 5 years postpartum. All data is also collated into a registry, which aims to assess the efficacy of the intervention at improving modifiable cardiovascular risk factors and reducing cardiovascular risk. Discussion: There is limited information on the efficacy of postpartum intervention clinics in reducing cardiovascular risk in women who have experienced pregnancy complications. Analyses of the data collected in the registry will provide essential information about how best to reduce cardiovascular risk in women in socioeconomically disadvantaged and disease-burdened populations.